ANÁLISIS FINANCIERO A LA “COOPERATIVA DE AHORRO Y CRÉDITO CARIAMANGA LTDA.” DE LA CIUDAD DE CARIAMANGA, PROVINCIA DE LOJA. PERIODOS 2015 – 2016 - Sarango Rueda, Jackeline Anabel (2018)
This thesis work called FINANCIAL ANALYSIS TO THE "COOPERATIVA DE AHORRO Y CRÉDITO CARIAMANGA LTDA." OF THE CITY OF CARIAMANGA, PROVINCE OF LOJA. PERIODS 2015-2016, was carried out in order to comply with one of the requirements established in the Academic Regulations in force prior to opting for the degree of Accounting Engineering and Public Accountant-Auditor Audit. To comply with the objectives, it was necessary to evaluate the structure of the Financial Statements, which allowed executing the vertical analysis of each study period, measuring the degree of representation of each account against the group to which it belongs and determining the financial structure, as well as well as knowing clearly how the financial statements are composed, that is to say if the distribution of the assets is equitable and goes according to the financial and operative needs of the cooperative; In addition, the horizontal analysis was carried out, establishing the financial movements and the variations that refer to the increases or decreases in the figures in the financial statements included in the 2015-2016 study periods. Subsequently, the indicators established by the regulatory body Superintendencia de Economia Popular y Solidaria (SEPS) were applied, which allowed measuring the economic and financial situation of the cooperative, by using the main indicators such as Capital, Structure and 5 Asset Quality, Microeconomic Efficiency, Profitability, Financial Intermediation, Financial Efficiency, Liquidity and Vulnerability of the Assets. Finally, the financial report has been developed with an easy-to-understand language so that managers and administrators know the results of the analysis and the real situation of the cooperative, putting the comments, conclusions and recommendations to consideration in order to help in the correct decision making. After applying the financial analysis the most relevant conclusion is that the Cariamanga Savings and Credit Cooperative Ltd. is not generating an appropriate return, since in 2015 it was 0.13% and in 2016 it was 0, 26%; evidencing that the income is not enough to strengthen the cooperative's assets; Likewise, when applying the Financial Intermediation indicator, it results in a percentage of 68.46% for the year 2015 and 56.91% for the year 2016, which indicates that the resources received from the partners through deposits to The sight and term are not being efficiently channeled through the different lines of credit.